Germanium gate hydrogen-terminated diamond field effect transistor with Al2O3 dielectric layer - Zhang Minghui; Wang Wei; Wen Feng; Lin Fang; Chen Genqiang; Wang Fei; He Shi; Wang Yanfeng; Fan Shuwei; Bu Renan; Min Tai; Yu Cui; et al. (Functional Diamond, 2022)
Investigation of germanium gate hydrogen-terminated (H-terminated) diamond field effect transistor (FET) with Al2O3 dielectric layer has been successfully performed. The device demonstrates a normally-on characteristics, whose maximum drain-source current density, threshold voltage, maximum transconductance, on/off ratio, subthreshold swing, capacitance, carrier density, saturation carrier mobility, fixed charge density and interface state density are of −37.3 mA/mm, 0.22 V, 6.42 mS/mm, 108, 134 mV/dec, 0.33 μF/cm2, 9.83 × 1012 cm−2, 97.9 cm2/V·s, 7.63 × 1012 cm−2 and 2.56 × 1012 cm−2·eV−1, respectively. This work is significant to the development of H-terminated diamond FET.